2017
DOI: 10.1163/26669323-04601005
|View full text |Cite
|
Sign up to set email alerts
|

Blurring the Boundaries: Integrating Techniques of Land Surveying on the Qing’s Mongolian Frontier

Abstract: This article focuses on the role of spatial dynamics in effectuating the integration of two different sets of land surveying techniques. During the later stages of the Qing-Zunghar wars of the 1690s, the Kangxi emperor (r. 1661-1722) repeatedly asked French Jesuit missionaries, who had been sent to China in 1685 under the patronage of the French King Louis XIV, to join his imperial campaigns targeting the Khalkha-Mongolian borderlands. In the shadow of these imperial journeys, missionaries systematically deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In this period, the emperor's broad political strategy as well as his own sheer intellectual interest was the main inspiration for map production. As Cams describes (2017, 31–35), the emperor used both European and Chinese cartographic practices to determine precisely the border between the Inner Mongolian lands and Qalqa / Khalkha (Outer Mongolia) (see further below). The ability to make maps for military purposes, ones that accurately reflected the great distances the emperor would lead his Qing armies against the Zhungars, was crucial at this time.…”
Section: The Political Conditions Of Production Of Mongol Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this period, the emperor's broad political strategy as well as his own sheer intellectual interest was the main inspiration for map production. As Cams describes (2017, 31–35), the emperor used both European and Chinese cartographic practices to determine precisely the border between the Inner Mongolian lands and Qalqa / Khalkha (Outer Mongolia) (see further below). The ability to make maps for military purposes, ones that accurately reflected the great distances the emperor would lead his Qing armies against the Zhungars, was crucial at this time.…”
Section: The Political Conditions Of Production Of Mongol Mapsmentioning
confidence: 99%
“…He was disturbed when experiments showed that the two methods did not coincide, concluded that the Chinese standards used in astronomical and cartographic practice were faulty, and in 1698 redefined the length of the li by imperial decree so that there were exactly 200 li in one degree of terrestrial latitude. Subsequently, other key measurements such as the smaller chi were redefined to conform (Cams 2017, 36–37). Many land surveys and maps, using the new li , were executed by mixed teams of European missionaries and Qing officials between 1708 and 1717.…”
Section: The Mongolian Maps In the Context Of Chinese And Tibetan Map...mentioning
confidence: 99%